STRATEGI WHATSAPP BLAST DALAM MENINGKATKAN FUNDRAISING PADA LEMBAGA AMIL ZAKAT PERSADA JAWA TIMUR - Moh. Bustanul Farihin Ma'aliy; Andriani Samsuri (ITB Swadharma, 2025)
This study analyzes the use of WhatsApp Blast as a digital communication strategy to increase fundraising at the Persada Zakat Institution (LAZ) in East Java. Using a descriptive qualitative approach through interviews, observations, and document analysis, this study explores the influence of WhatsApp Blast on donor decisions and the role of trust in strengthening their loyalty. The results show that WhatsApp Blast is effective at reaching donors quickly, personally, and in large numbers at an efficient cost compared to conventional methods. The application of Integrated Marketing Communication (IMC) principles and segmentation, targeting, and positioning (STP) strategies has been proven to support increased donor participation, especially during religious moments. In addition, transparency in information, accountability in reporting, and personal communication via WhatsApp Blast strengthen donor trust, a key factor in donation decisions. However, the effectiveness of this strategy is greatly influenced by segmentation, content quality, and the timing of message delivery. This study confirms that optimizing WhatsApp Blast can increase fundraising success and strengthen long-term relationships between institutions and donors.Penelitian ini menganalisis pemanfaatan WhatsApp Blast sebagai strategi komunikasi digital dalam meningkatkan fundraising pada Lembaga Amil Zakat (LAZ) Persada Jawa Timur. Dengan pendekatan kualitatif deskriptif melalui wawancara, observasi, dan analisis dokumen, penelitian ini mengeksplorasi pengaruh WhatsApp Blast terhadap keputusan donatur serta peran kepercayaan dalam memperkuat loyalitas mereka. Hasil penelitian menunjukkan bahwa WhatsApp Blast efektif dalam menjangkau donatur secara cepat, personal, dan masif dengan biaya efisien dibandingkan metode konvensional. Penerapan prinsip Integrated Marketing Communication (IMC) serta strategi segmentasi, targeting, dan positioning (STP) terbukti mendukung peningkatan partisipasi donatur, khususnya pada momentum keagamaan. Selain itu, transparansi informasi, akuntabilitas laporan, dan komunikasi personal melalui WhatsApp Blast memperkuat kepercayaan donatur, yang menjadi faktor kunci dalam keputusan berdonasi. Kendati demikian, efektivitas strategi ini sangat dipengaruhi oleh segmentasi, kualitas konten, serta waktu pengiriman pesan. Penelitian ini menegaskan bahwa optimalisasi WhatsApp Blast berpotensi meningkatkan keberhasilan fundraising dan memperkuat hubungan jangka panjang antara lembaga dan donatur.